Borderline Personality Disorder in Adolescence as a Generalization of Disorganized Attachment - Miljkovitch, Raphaële; Deborde, Anne-Sophie; Bernier, Annie; Corcos, Maurice; Speranza, Mario; Pham-Scottez, Alexandra (Frontiers in Psychology, 2018)
Several researchers point to disorganized attachment as a core feature of borderline personality disorder (BPD). However, recent studies suggest that specific internal working models (IWMs) of each parent combine to account for child outcomes and that a secure relationship with one parent can protect against the deleterious effects of an insecure relationship with the other parent. It was thus hypothesized that adolescents with BPD are more likely to be disorganized with both their parents, whereas non-clinical controls are more secure with at least one of their caregivers. Thirty-six adolescents with BPD and 30 control participants (aged 13-19) were included. Psychiatrist diagnosis was verified with the SIDP-IV and comorbidity was assessed using the Kiddie-SADS. Reported trauma was assessed with the Childhood Trauma Questionnaire. Attachment IWMs of each parent were assessed with the Attachment Multiple Model Interview (AMMI), which enables separate coding for each attachment figure and in which disorganization is conceptualized as conflicting attachment strategies within a specific relationship. Results of a logistic regression analysis suggested that beyond insecure attachment, being disorganized not just with one but with both parents is particularly characteristic of adolescents with BPD. Conversely, belonging to the non-clinical group was predicted by higher security scores with the father and lower deactivation with the mother. Although higher levels of childhood abuse or neglect were reported by adolescents with BPD, the retained attachment dimensions predicted group membership over and above reported trauma. These findings have important implications for clinical intervention and highlight the protective role fathers may have.